Extended dissipative analysis for aircraft flight control systems with random nonlinear actuator fault via non-fragile sampled-data control. Issue 15 (October 2019) - Zhu, Quanxin; Vimal Kumar, S.; Raja, R.; Rihan, Fathalla
Abstract: This paper addresses the issue of reliable feedback control of an uncertain aircraft flight control systems with disturbances via non-fragile sampled-data control approach. In particular, the parameter uncertainties are assumed to be randomly occurring which is described by the Bernoulli distributed sequences. By constructing a suitable Lyapunov–Krasovskii functional together with Wirtinger-based inequality, a new set of sufficient conditions in terms of linear matrix inequalities is obtained to ensure the asymptotic stability and extended dissipativity of the aircraft flight control systems not only when all actuators are operational, but also in case of some actuator failures. Finally, simulation results are conducted to validate the effectiveness of the proposed control design technique.